Building a Way to the City? Asking about Objects, Conditions, and Essence as a Methodology for Approaching the Urban - Vacher, Mark (Hamburger Journal für Kulturanthropologie (HJK), 2019)
Der Artikel beschäftigt sich mit der Frage: Was macht die Stadt zu dem, was sie ist? Auch wenn Fragen für gewöhnlich eine Antwort fordern, zeigt der Beitrag, dass es auch andere Wege gibt, sich ihnen zu nähern. Inspiriert vom Philosophen Martin Heidegger eröffnet er auch die Strategie, mit sensiblem Fragen das Befragte einzuladen, sich nicht nach bestehenden Definitionen zu präsentieren, sondern authentisch, zu seinen eigenen Bedingungen. The purpose of this paper is to address a question: what makes a city what it is? Admittedly, asking a question usually aims at finding an answer, but, as I will explain in the following, there are other ways to approach questions. Inspired by the German philosopher Martin Heidegger, and in particular his lecture on ›The Question Concerning Technology‹, I will demonstrate that sensible questioning can work as an invitation for the object questioned in this way to reveal itself, not as a captive caught in pre-established definitions, but as an authentic being revealing itself on its own terms.